Design and approval of the nutritional warnings' policy in Peru: Milestones, key stakeholders, and policy drivers for its approval. - Francisco Diez-Canseco; Victoria Cavero; Juan Alvarez Cano; Lorena Saavedra-Garcia; Lindsey Smith Taillie; Francesca R Dillman Carpentier; J Jaime Miranda (Public Library of Science (PLoS), 2023)
Nutritional warnings are used as a public health strategy to address obesity. Peru approved in 2013 and implemented in 2019 a law requiring nutritional warnings on the marketing and packaging of processed foods high in sugar, sodium, saturated fat, and containing trans-fat. The complexity behind the design and approval of these policies over six years provides unique learnings, that inform the obesity prevention context, especially when proposed policies face strong opposition from powerful stakeholders. Our study aims to describe the milestones and key stakeholders' roles and stances during the nutritional warnings policy design in Peru, and to identify and analyze the main drivers of policy change that explain its approval. In 2021, interviews were conducted with 25 key informants closely involved in its design. Interviews were analyzed using the Kaleidoscope Model as a theoretical framework. Relevant policy documents and news were also analyzed. Milestones for this policy included the approval of the Law, Regulation, and Manual. Policy supporters were mainly from Congress, civil society advocates, and Health Ministers. Opponents came from Congress, ministries linked to the economic sector, the food industry, and media. Across the years, warnings evolved from a single text, to traffic lights, to the approved black octagons. Main challenges included the strong opposition of powerful stakeholders, the lack of agreement for defining the appropriate evidence supporting nutritional warning parameters and design, and the political instability of the country. Based on the Kaleidoscope Model, the policy successfully targeted a relevant problem (unhealthy eating decisions) and had powerful advocates who effectively used focusing events to reposition the warnings in the policy agenda across the years. Negotiations weakened the policy but led to its approval. Importantly, government veto players were mostly in favor of the policy, which enabled its final approval despite the strong opposition.